Electrodiagnostic Studies in Degenerative Cervical Myelopathy. Issue 10 (1st December 2022) - Davenport, Ryan; Jandzinski, Michal; Ahmed, Muhammad; Stino, Amro; Aleem, Ilyas
Abstract : The diagnosis of degenerative cervical myelopathy can generally be made with a thorough history, physical examination, and spinal imaging. Electrodiagnostic studies, consisting of nerve conduction studies and electromyography, are a useful adjunct when the clinical picture is inconsistent or there is concern for overlapping pathology. Electrodiagnostic studies may be particularly helpful in identifying cases of myeloradiculopathy, when there is combined nerve root and spinal cord injury, both with regards to prognosis and guiding surgical treatment. Electrodiagnostic studies are a useful adjunct for the spine surgeon and should be used when there are features atypical for degenerative cervical myelopathy or when there is suspicion for a concomitant disease process.